Eustachian Tube Foreign Body with Endoscopic-Assisted Surgical Removal - Phillip R. Purnell; Adam Bender-Heine; Habib Zalzal; Abdul R. Tarabishy; Adam Cassis (Case Reports in Otolaryngology)
Objectives. Foreign bodies of the external and middle ear are not uncommon; however, foreign bodies in the eustachian tube are rare. Here we describe the presentation, imaging, and endoscopic-assisted surgical management of a case of eustachian tube foreign body. Methods. A 34-year-old male was seen for evaluation of foreign body of the left eustachian tube while working with metal at a machine shop. Imaging and surgical management are highlighted and review of available literature regarding foreign bodies of the eustachian tube is presented. Results. A CT scan revealed a foreign body present approximately 1 cm into the bony eustachian tube. The patient underwent middle ear exploration which required endoscopic assistance to adequately visualize the foreign body. The foreign body was unable to be removed and required the creation of a bony tunnel lateral to the eustachian tube for visualization and access to the foreign body. Conclusions. This report presents a rare case of eustachian tube foreign body. Use of the endoscope during the surgical removal greatly enhanced the ease and safety of removal. This report also highlights the importance of ear protection with any machining and welding work.